Rectourethral fistula following SpaceOAR gel placement for prostate cancer radiotherapy: A rare complication - Joshua M. Kuperus; Donald G. Kim; Tanmay Shah; George Ghareeb; Brian R. Lane (Urology Case Reports, 2021)
After undergoing a SpaceOAR® gel placement prior to planned radiotherapy for Gleason 4 + 4 prostate cancer, a 70-year-old male experienced severe right buttock pain and urine passing from his rectum. A colonoscopy and follow-up pelvic MRI demonstrated a large rectourethral fistula. The fistula was treated surgically with a robot-assisted radical prostatectomy, primary rectal repair, omental flap and diverting loop ileostomy. Pathology demonstrated extensive treatment effect with no residual prostate cancer. This is the first case study of a rectourethral fistula attributable to SpaceOAR® gel placement.